علاقة الوظائف الداعمة لإدارة علاقة الزبون بتحقیق المیزة التنافسیة في قطاع الاتصالات دراسة حالة: موبیلیس للفترة الممتدة )جویلیة 2018إلى غایة سبتمبر (201 - بوضیاف , إلیاس (Finance and Business Economies Review, 2018)
Relationship Marketing is a new marketing paradigm, that based on customer focus, operations and procedures to meet the needs efficiently and the least cost and effort, thereby maximizing the profits of the organization and customer. We aim through this study mainly to measure the relationship between customer relationship management, in developing the competitive advantage through their supported functions. By building a model that shows the relationship between the variables studied (Customer relationship management and competitive advantage) with its dimensions. This study has been conducted on a sample of 22 agency of the telecom operator of ‘Mobilis’, relying on survey method to collect and analyze information by set of statistical indicators, with using of statistical program SPSS V20 .through using T test to validate hypotheses. The main results of this study show the existence of indicators that proofs the relationship between customer relationship management adoptions by ‘Mobilis’and its contribution on achieve the competitive advantage